The Impact of Financial Proficiency, Financial Attitudes, and Income on Financial Behavior in Using PayLater on E-Commerce - Nur Komarudin, Munir; Arraniri, Iqbal; Agyan, Dea Fadhila (Asosiasi Ahli Administrasi Indonesia, 2024)
This research aims to determine the influence of financial proficiency, financial attitudes and income on the financial behavior of using Paylater in millennial generation E-Commerce in Kuningan. The research method used is descriptive with a quantitative approach. The sampling technique used was non-probability sampling with an incidental sampling and purposive sampling approach totaling 400 respondents. Data collection was carried out by distributing questionnaires in the form of a Google form. Hypothesis testing in this research uses multiple linear analysis tests. The research results show that financial literacy, financial attitudes and income have a positive effect on financial behavior.